IMPLEMENTASI MODEL CONCEPT ATTAINMENT UNTUK MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH - Handayani, Ratnawati; Hidayati, Yulia Maftuhah (Profesi Pendidikan Dasar, 2020)
This study aims to describe the implementation of concept attainment model in developing math problem solving skills of 5th grade elementary school students. This study used a qualitative approach with a phenomological research design. The subjects in this study were 2 students and 1 teacher of 5th grade of SD Negeri Newung 2 Elementary School (SDN Newung 2), Sukodono, Indonesia. The data technique used tests and interviews with students and teachers. The data validity used source and method triangulation. Data analysis used three stages, namely (1) data reduction, (2) data presentation, (3) data conclusions. The results of this study, (1) the students' mathematical solving ability is good, because students have mastered the indicators of mathematical problem solving abilities, (2) Implementation of the concept attainment model in Mathematics learning is correct, because students are enthusiastic about learning, the steps used are appropriate, namely the stage of analyzing thinking strategies, presenting data, and testing concept achievement.